„Trzeba to wszystko zniszczyć”. Ostatnia pieśń ze Śpiewnika włoskiego - Mitzner, Piotr (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
This essay discusses a controversial yet not entirely obvious aspect of Jarosław Iwaszkiewicz’s oeuvre, namely his anarchist rebellion against tradition. The line from one of the poet’s late poems quoted in the title above expresses the belief permeating Iwaszkiewicz’s works starting with his early futurist poems and ending with a story “Notre-Dame-La Grande”, which was written on the wave of the student revolt in 1968. The argument is that Iwaszkiewicz should no longer be perceived only as a guardian of tradition.